2019
DOI: 10.1002/aoc.5446
|View full text |Cite
|
Sign up to set email alerts
|

Effectively promoted catalytic activity by adjusting calcination temperature of Ce‐Fe‐Ox catalyst for NH3‐SCR

Abstract: A series of Ce‐Fe‐Ox catalysts prepared by the different calcination temperatures (marked as CF‐X, where X represented calcination temperature) were used to the selectivity catalytic reduction of NOx by NH3. The results explained the relationship between calcination temperature and the sulfate species over Ce‐Fe‐Ox, and then investigated the surface acidity and catalytic performance. The large amounts of sulfate species were formed over CF‐450 and CF‐550 while it was decomposed with further the increasing of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…For this purpose, many catalysts containing metal oxides have been found to possess high catalytic activity for SCR reaction including Fe, Ce, Mn, and Cu based catalysts. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Based on our previous study, we found the Fe-Ce/Ti catalysts could exhibit high catalytic activity for the NH 3 -SCR reaction. However, there are several components in the real ue gases including K, Ca, CO 2, and SO 2 , which will lead to the physical or chemical deactivation of catalysts and thus restrict the industrial application of catalysts.…”
Section: Introductionmentioning
confidence: 90%
“…For this purpose, many catalysts containing metal oxides have been found to possess high catalytic activity for SCR reaction including Fe, Ce, Mn, and Cu based catalysts. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Based on our previous study, we found the Fe-Ce/Ti catalysts could exhibit high catalytic activity for the NH 3 -SCR reaction. However, there are several components in the real ue gases including K, Ca, CO 2, and SO 2 , which will lead to the physical or chemical deactivation of catalysts and thus restrict the industrial application of catalysts.…”
Section: Introductionmentioning
confidence: 90%
“…As it can be seen the strength and the number of acid sites are clearly affected by the type of the elements added to titania oxide. So, the highest total acidity is obtained in the case of V 2 O 5 -WO 3 -TiO 2 catalyst which displays the most intense and large NH 3 desorption peaks between 100 and 550 °C corresponding to the ammonia desorbed from weak, medium and strong acid sites [47,65]. As shown also in Fig.…”
Section: Characterization Of Aerogel Catalystsmentioning
confidence: 99%
“…O ɑ is more active than O ⊎ due to its mobility. 42,43 Suitable improvement of the O ɑ proportion was helpful for NO x conversion.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the results of XRD and H 2 ‐TPR, it was believed that more oxygen vacancies formed in Fe 9 CeO x ‐N 2 , resulting in more surface‐adsorbed oxygen species. O ɑ is more active than O β due to its mobility 42,43 . Suitable improvement of the O ɑ proportion was helpful for NO x conversion.…”
Section: Resultsmentioning
confidence: 99%